2007
DOI: 10.1007/s10464-007-9088-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors for urban African‐American youth

Abstract: The present study investigated risk and resilience processes in a sample of urban African-American youth. Risk and protective factors were assessed across ecological levels including individual, family and community. Both externalizing and internalizing symptomatology were included as measures of child adjustment. Youth and parental reports as well as various methods, such as the Experience Sampling Method, were used to capture the daily experiences of the adolescents from different perspectives. Poverty, hass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
105
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(132 citation statements)
references
References 65 publications
12
105
1
2
Order By: Relevance
“…More generally, however, the finding that positive family functioning may not serve a protective function at high levels of risk is corroborated by several studies (e.g., Li et al 2007). For example, a study of predominantly ethnic minority, low-income boys found that low family conflict was only protective in the context of low community violence exposure (Miller et al 1999).…”
Section: Moderating Role Of Neighborhood Disadvantage Trajectoriesmentioning
confidence: 81%
“…More generally, however, the finding that positive family functioning may not serve a protective function at high levels of risk is corroborated by several studies (e.g., Li et al 2007). For example, a study of predominantly ethnic minority, low-income boys found that low family conflict was only protective in the context of low community violence exposure (Miller et al 1999).…”
Section: Moderating Role Of Neighborhood Disadvantage Trajectoriesmentioning
confidence: 81%
“…Religious support involves receiving social support through being connected with a religious congregation (Pargament, 1997). Social support is a protective factor for youth that is related to positive youth development (Travis & Leech, 2013), can enhance adaptation (DuBois et al, 2002), and buffer against stressors (Hammack, Richards, Luo, Edlynn & Roy, 2004;Li, Nussbaum & Richards, 2007;Paxton, Robinson, Shah & Schoeny, 2004). In this study we assessed support adolescents receive from church members, church leaders, and God.…”
Section: Religious Supportmentioning
confidence: 99%
“…Although there is growing research on positive youth development and Afrocentric approaches over the past two decades (e.g., Watts, Williams & Jagers, 2003), much of the existing psychological literature on African-American adolescent development focuses on negative outcomes (Eitle, Gunkel & Van Gundy, 2004;McGee, 2003); the inclusion of positive elements in the lives of youth are often conceptualized as buffers for negative influences or preventative factors for negative outcomes (e.g., Brook & Pahl, 2005;Jagers et al, 2007;Li et al, 2007). While there is an increasing focus on positive factors in the lives of adolescents leading to positive outcomes, more strengths-based research and more integration of positive and negative contributors to a range of positive and negative outcomes is necessary to fully understand the developmental processes of African-American adolescents.…”
Section: Researchmentioning
confidence: 99%
“…This paper aims to show how the restorative justice system is applied in Italy, and by referring to Walgrave's studies (1995Walgrave's studies ( , 1998Walgrave's studies ( , 2008, concerning the history and assumptions of restorative justice, Winterdyk's research (1997), into how the system is applied and works in practice, and studies into the results obtained from restorative justice and reoffending (Bergseth & Bouffard, 2007, Pranis, 1998, Bazemore 2007, highlight both its critical aspects and favourable outcomes. This paper demonstrates that there is a need to develop skills in the community, in order to counter community conditions, such as limited resources, limited educational opportunities, lack of leisure facilities and opportunities, which encourage juvenile delinquency (Li et al, 2007;Sprott, Jenkins & Doob, 2005;Brown et al, 1997;Cottle et al, 2001;Walker et al, 1996).…”
Section: Introductionmentioning
confidence: 96%